A Comparison Between the Patterns of CN, O, and Na Inhomogeneities on the Red Giant Branch of Messier 71 Using Data from the Literature. (4th January 2016) - Smith, Graeme H.
Abstract: Data drawn from the published literature are used to define the relations between the spectroscopic λ4215 CN-band strength of red giants in the globular cluster Messier 71 and both the sodium and oxygen abundances. The cluster giants with CN measurements included in this study have absolute magnitudes in the range -2 <  M V  < +2. The data are consistent with a moderate degree of anticorrelation between the CN-band strength and the [O/Fe] abundance, as well as a moderate correlation between CN-band strength and [Na/Fe], although there is scatter of up to 0.3-0.4 dex in both O and Na abundance among giants with CN bands of similar strength. The mean difference in [O/Fe] between CN-strong and CN-weak giants is 0.13 dex, the former group of stars having the lower average oxygen abundance. By contrast, the mean difference in [Na/Fe] between CN-strong and CN-weak giants is 0.17 dex, with the CN-strong group having the higher average sodium abundance. There is a similar range in λ4215 CN-band strengths among the red giants in Messier 71 and 47 Tucanae. Furthermore, the red giant branch stars in the two clusters follow very similar relations between CN-band strength and [Na/Fe] abundance. These two similarities are intriguing given that the two clusters differ by a factor of 30 or more in luminous mass, with 47 Tuc having a much higher degree of central mass concentration than M71. A difference can be discerned between the O-CN relations in the two clusters, such that for a given CN-band strength the CN-strong giants in 47 Tuc attain lower values of [O/Fe], a result that is consistent with previously noted differences in the O-Na relations of the two objects. A scenario is discussed in which both 47 Tuc and M71 were formed as the mergers of pre-existing CN-weak and CN-strong subclusters, the later having been formed following chemical evolution and self-enrichment of a large cloud complex that had earlier formed the CN-weak subcluster. Different dynamical merger routes may have lead in one instance to the high-mass 47 Tuc cluster, whereas M71 may have resulted from a merger that was accompanied by a large amount of star loss and stellar evaporation.